Nihajoča asimetrija (s poudarkom na asimetriji Rogovja cervidov) kot zgodnji kazalec stresa - Pokorny, Boštjan (Zbornik gozdarstva in lesarstva, 2004)
Fluctuating asymmetry (FA), which reflects non-directional and stress-induced differences between the left and the right side of otherwise perfect symmetrical bilateral traits, may be a useful sensitive bioindicator of stressful conditions in many wildlife species. However, in spite of their great potential, FA analyses present an almost unknown research field in Slovenia. Therefore, the following issues are discussed at greater length in the paper: (a) the most important principles, advantages and drawbacks of FA analyses; (b) a review of recent findings on the influence of some stressors on FA of bilateral traits in different wildlife species; (c) influence of heavy metals on FA of selected animal traits/organs; (d) a review of existing findings on asymmetry of antlers/horns in wildliving ungulates. As such, this review paper is important for a well-grounded presentation of our own work on roe deer antlers, and particularly for understanding the employability of roe deer antlers as an excellent tool for bioindication of environmental pollutionwith inorganic pollutants (companion paper).
Keywords: bioindikatorji; jeleni; rogovje; simetrija; srnjad; stres